Impostor syndrome and pretense - Levy, N (Taylor and Francis, 2022)
Impostor Syndrome is the belief or feeling that one is passing oneself off as much more capable than one really is. Anecdotally, it is experienced more by members of historically disadvantaged groups, but the empirical data seems inconsistent with this view. I argue that impostor syndrome occurs because (a) it is normal, appropriate and often even necessary to engage in some degree of pretense in order to acquire specialist expertise, but (b) we are much more likely to be aware of our own pretense than that of others. I argue that we are especially likely to notice pretense when we’re made self-conscious, and that failing to match the stereotype of one’s profession or domain of expertise tends to give rise to self-consciousness. Self-consciousness is elicited by certain cues; this fact explains not only the greater vulnerability of the members of some groups to it, but also explains why the empirical data has not yet provided evidence for this greater vulnerability. I end with some suggestions for reducing the prevalence or impact of impostor syndrome.